2003
DOI: 10.1152/ajpheart.00403.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oral antioxidant therapy improves endothelial function in Type 1 but not Type 2 diabetes mellitus

Abstract: Oxidative stress decreases the bioavailability of endothelium-derived nitric oxide in diabetic patients. We investigated whether impaired endothelium-dependent vasodilation (EDV) in diabetes can be improved by long-term administration of oral antioxidants. Forty-nine diabetic subjects [26 Type 1 (T1) and 23 Type 2 (T2)] and 45 matched healthy control subjects were randomized to receive oral vitamin C (1,000 mg) and vitamin E (800 IU) daily or matching placebo for 6 mo. Vascular ultrasonography was used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 56 publications
5
87
0
3
Order By: Relevance
“…The response to nitroglycerin was attenuated in subjects with type 2 diabetes and lipodystrophic diabetes. We have previously reported an impaired response to nitroglycerin in subjects with type 2 diabetes (44), but this is the first report of a similar finding in subjects with lipodystrophic diabetes. Markers of insulin resistance, adipokines, and inflammation did not associate with vascular smooth muscle function.…”
Section: Potential Mediators Of Endothelial Dysfunction In Insulin Rementioning
confidence: 54%
See 1 more Smart Citation
“…The response to nitroglycerin was attenuated in subjects with type 2 diabetes and lipodystrophic diabetes. We have previously reported an impaired response to nitroglycerin in subjects with type 2 diabetes (44), but this is the first report of a similar finding in subjects with lipodystrophic diabetes. Markers of insulin resistance, adipokines, and inflammation did not associate with vascular smooth muscle function.…”
Section: Potential Mediators Of Endothelial Dysfunction In Insulin Rementioning
confidence: 54%
“…Glucose levels correlated inversely with smooth muscle function. The attenuation in endothelium-independent vasodilation may relate to chronic hyperglycemia as reflected in attenuation of nitroglycerin-mediated vasodilation in diabetes (44,45). Despite the attenuation in endothelium-independent vasodilation in the subjects with lipodystrophic diabetes, flow-mediated, endotheliumdependent vasodilation was preserved.…”
Section: Potential Mediators Of Endothelial Dysfunction In Insulin Rementioning
confidence: 97%
“…In a recent study, combined therapy with vitamins C and E in types I and II diabetic patients showed an improvement in endothelial function only in type I diabetic patients. 54 In another study, high oral doses of vitamin C did not improve endothelial function in type II diabetic subjects. 55 Interestingly, in this study, although the diabetic patients with low vitamin C levels were able to replenish their vitamin C levels with the high-dose oral supplementation, they did not achieve as high levels as healthy non-diabetic subjects.…”
Section: Human Studiesmentioning
confidence: 94%
“…Again it may be pointed out that this association was not significant. Beckman et al (128) reported that administration of vitamin E and C in the doses of 800 IU/d and 1000 mg/d respectively for six months alleviated vasorelaxation in DMT-1 but not in DMT-2. Another A combination of vitamins E and C in the doses of 680 mg/d and 1250 mg/d improved renal function in DMT-2 patients.…”
Section: Antioxidant Therapy and Supplementsmentioning
confidence: 99%